Motivational factors influencing women’s decisions to pursue upper-level administrative positions in higher education - Cox, Kelline Sue (Kansas State University, 2008)
Much of the research on women advancing in higher education has been focused on the external barriers and how to break down the barriers. Initiatives and programs have been implemented, but the number of women in upper-level administrative positions in higher education, although increasing, is not increasing in proportion to women's overall numbers in education and the work force. The structure and processes at work in a particular situation can change more readily than changing people's behaviors directly. With this in mind, the purpose of this study was to take a positive approach by looking to women who have reached the upper-level administrative arena and investigate what influential factors were responsible for motivating them to this achievement. This qualitative multi-case study used the elements of Bandura's Model of Reciprocal Determination, specifically self-efficacy, personal behavior, and environmental factors to determine the factors motivating women to upper-level administrative positions. Eighteen women who have reached the upper-level administrative positions (e.g., provost, vice-president or vice-provost) at land-grant universities were interviewed. The themes of this study suggest that support groups and individual mentors were important motivating factors because these groups and individuals encouraged, coached, and supported women administrators on their decisions to enter higher education and then as they pursued upper-level administrative positions. In addition, women felt successful when they were able to be the nurturers, assisting and influencing others to succeed. Also, the women administrators recognized the need for knowledge, skills, and experience to assist in their career advancement. Furthermore, they emphasized developing and evaluating personal values, and ensured their personal values fit with institutional values. At the same time, women administrators stressed the value of time and the choices they made to balance time between work and family and between work and personal time. Recommendations to implement initiatives to promote and support the motivational factors identified in this study are discussed.
Keywords: Motivation; Women administrators; Higher education; Bandura's model of reciprocal determination; Mentoring; Value system; Education, Administration (0514); Women's Studies (0453)